Efektifitas Teknik Relaxaxi Terhadap Pengurangan Rasa Nyeri Persalinan Kala I Di BPS Ny. Yohana Dian, Amd. Keb. Desa Sumbertanggul Mojosari Mojokerto - Hety, Dyah Siwi (SEKOLAH TINGGI KESEHATAN MAJAPAHIT MOJOKERTO, 2014)
One of means for giving comfortable to mother who is delivery baby, is with doing decrease delivery pain technic, for example relaxation, because this relaxation able decrease tight and individual preseption about pain, beside that relaxation technic not dangerous for fetus and mother, the result from this experiment for knowing effectiveness giving relaxation technic to decrease pain of delivery first period.Kind of the experiment is use pre experimental with post test only control group design. Variable independent in this experiment is relaxation technic and variable dependent is decrease pain delivery first period with population 13 mothers. Get sample in this experiment according accidental sampling. Time this experiment, june 10th - August 23th, 2009 and place this experiment BPS. Ny Yohana, Amd.Keb analytical data technic using independent sample t-test, aggregation data technic using primer data, with association data instrument using obaservation sheet and check list . Pain on respondens who is not giving relaxation technic mayority cause serious pain they are 4 respondens or about 66.67 %. And pain on respondens who is giving relaxation mayority cause medium pain they are 3 respondens or about 42.86 %. Grounded on that, the mother group that given relaxation technic (treatment grup) got pain more minor than the mother grup that not given relaxation technic (control group), pain effected by some factors, they are old, education, job, and paritas, beside that the decrese pain of delivery on the treatment group is done by relaxation and suggestion from the midwife , so the pains can be minimazed. Examinationâs effectivity of relaxation technic for pain decrease get from t-test analisa and the result thitung bigger than ttable (9. 90>2.50), of course H0 refused and H1 accepted.The conclusion is technic relaxation efektive for decrease pain delivery first period. The researcher suggestion for the experimentâs place to evolving, give information about relaxation technic, and able to do relaxation technic to all patients who is delivery babys as constant procedure in delivery for decrease pain on first period delivery.Keywords : Relaxation, Pain of delivery